ANALISIS PERBANDINGAN NILAI TEORI DENGAN PRAKTIK SERVICE EXCELLENCE PADA DIVISI KEAMANAN SUMMARECON MALL SERPONG - Salsabil, Sarah Alya (Publika Citra Media, 2024)
Summarecon Mall Serpong is a shopping center in the Tangerang area. Visitorswho enter the mall area for the first time will feel unfamiliar with its location. Ingeneral, visitors who come for the first time will ask the security division officer,then the security officer will help in answering the question. If the service providedby security division officers is not good, it will cause complaints from visitors. Oneof the efforts is to carry out excellent service training. The research method used inthis research uses quantitative research with a type of comparative research wherethe data is obtained using primary data. The techniques for collecting primary dataare through questionnaires and observation. Questionnaires are filled in bytraining participants to see their theoretical values and observations are carriedout by observers (mystery guests) who will fill in the form, to see their practicalvalues. The observation form contains statements on a 1-10 Likert scale. Samplecollection was used using non-probability with a purposive sampling techniquewhere samples were obtained from 50 people from the security division. Theresearch was analyzed using non-parametric inferential statistics using theKolmogorov Smirnov normality test and the Wilcoxon test method. The researchresults show that there is a difference between theoretical values and observationalvalues after excellent service training.